2004
DOI: 10.1007/s11745-004-1239-x
|View full text |Cite
|
Sign up to set email alerts
|

CLA isomers in milk fat from cows fed diets with high levels of unsaturated fatty acids

Abstract: The concentrations of CLA isomers were determined by Ag+ -HPLC in the milk fat of cows fed a control diet consisting of hay ad libitum and 15 kg of fodder beets or this diet supplemented with oilseeds containing either high levels of oleic acid (rapeseed), linoleic acid (sunflower seed), or alphalinolenic acid (linseed). Highly significant (P < or = 0.001) correlations were found between the daily intakes of oleic acid and the concentration of the CLA isomer trans-7,cis-9 in milk fat; of linoleic acid and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
108
2
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(146 citation statements)
references
References 43 publications
34
108
2
2
Order By: Relevance
“…A markedly different distribution of CLA isomers in duodenal digesta in this experiment with trans-11 trans-13 CLA and trans-12 trans-14 CLA predominating may reflect diets being based on forages rich in C18:3n-3 and relatively low in C18:2n-6. Previous studies have shown that supplementing the diet with linseed oil rich in C18:3n-3 enhances the flow of both these isomers at the duodenum (Loor et al, 2004) and omasum (Shingfield et al, 2003) and increases their concentrations in milk fat (Collomb et al, 2004;Loor et al, 2005a, Roy et al, 2006. The increasing importance of trans-11 cis-13 CLA with FO addition on both silages may also suggest a change in the action of biohydrogenation in the presence of FO.…”
Section: Rumen Functionmentioning
confidence: 96%
“…A markedly different distribution of CLA isomers in duodenal digesta in this experiment with trans-11 trans-13 CLA and trans-12 trans-14 CLA predominating may reflect diets being based on forages rich in C18:3n-3 and relatively low in C18:2n-6. Previous studies have shown that supplementing the diet with linseed oil rich in C18:3n-3 enhances the flow of both these isomers at the duodenum (Loor et al, 2004) and omasum (Shingfield et al, 2003) and increases their concentrations in milk fat (Collomb et al, 2004;Loor et al, 2005a, Roy et al, 2006. The increasing importance of trans-11 cis-13 CLA with FO addition on both silages may also suggest a change in the action of biohydrogenation in the presence of FO.…”
Section: Rumen Functionmentioning
confidence: 96%
“…Forage source can alter the distribution of specific milk fat CLA isomers depending on FA composition. The increases in trans-10, trans-12 CLA and trans-7, cis-9 CLA observed with increasing MS inclusion could reflect biohydrogenation of the principle FA in MS, 18:2n-6 (Collomb et al, 2004;Roy et al, 2006), whereas the decreases in trans-12, trans-14 CLA, trans-11, trans-13 CLA and trans-11, cis-13 CLA can be attributed to the decreased intake of the principle FA in GS (18:3n-3) with increasing MS inclusion (Collomb et al, 2004;Roy et al, 2006).…”
Section: --mentioning
confidence: 99%
“…Collomb et al [11] found in a study of 44 milk samples from three different regions in Switzerland (lowlands, mountains and highlands) CLA concentrations of 0.87, 1.61 and 2.36 g·100 g -1 lipid, respectively. It was found that the CLA content in milk is influenced by the cows' diet [11,12,40,62,66]. Ledoux et al [38] found important differences in CLA content between summer and winter butter (0.80 and 0.45 g CLA·100 g -1 butter, respectively).…”
Section: Introductionmentioning
confidence: 99%